Climate change will alter Amazonian bumblebees’ distribution, but effects are species-specific - Nunes-Silva, Patrícia; Acosta, André Luis; Borges, Rafael Cabral; Freitas, Breno Magalhães; Oliveira, Ricardo Caliari; Giannini, Tereza Cristina; Imperatriz-Fonseca, Vera Lucia (Frontiers in Bee Science, 2025)
IntroductionUnderstanding how climate change affects the distribution of Amazonian bumblebee species is essential for their conservation and the pollination services they provide. This study focuses on two poorly known species, Bombus brevivillus and Bombus transversalis, evaluating how future climate scenarios may alter their suitable habitats in the Brazilian Amazon. Identifying potential refugia and vulnerable areas is crucial for developing targeted conservation strategies.MethodsSpecies distribution models were applied using occurrence data from museum records and field collections. Climatic suitability was projected under the baseline period (1970–2000) and two future periods (2021–2040 and 2041–2060) using the high-emission scenario (SSP5-8.5) from the IPCC AR6 report. An ensemble modeling approach combining five different algorithms was used to predict areas of stability, habitat loss, and potential range expansion.ResultsBy 2060, B. brevivillus is projected to lose 41.6% of its current suitable habitat, with significant reductions in northern and coastal regions. Conversely, B. transversalis is expected to retain 89.5% of its current range, showing a westward distribution shift. New climatically suitable areas may emerge for both species, particularly in the western Amazon, potentially serving as future refugia.DiscussionThe findings highlight species-specific responses to climate change, with B. brevivillus being more vulnerable than B. transversalis. These results emphasize the need for proactive conservation measures to protect critical habitats and mitigate the impacts of climate change. Future research should focus on assessing thermal tolerance and habitat connectivity to refine conservation strategies and ensure the persistence of these essential pollinators in changing environmental conditions.